Upaya Guru dalam Meningkatkan Kemampuan Literasi Siswa melalui Pojok Baca di MI Salamah Kota Jambi - Isfana Salsabilla; Saidah Ahmad (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study was motivated by the condition of students who are still lacking in literacy activities carried out by the school in the morning 15 minutes before learning begins. This study aims to determine Teacher Efforts in Improving Students' Literacy Skills through the Reading Corner at MI SALAMAH Jambi City, the method used in this study is qualitative using data collection instruments in the form of observation, interviews and documentation. The data sources are the Principal, Class Teachers, and students, Data analysis techniques used are Data Reduction, Data Display, and Conclusions. The results of this study indicate that, Teacher Efforts in Improving Students' Literacy Skills through the Reading Corner at MI Salamah Jambi City have been implemented well, for example, children can already speak well and correctly but there are also those who still cannot speak correctly. Supporting and inhibiting factors in Teacher Efforts in Improving Students' Literacy Skills through the Reading Corner at MI Salamah Jambi City, The supporting factors are such as facilities and infrastructure, having a reading corner in the classroom, and environmental factors. While the inhibiting factors are, the books in the reading corner are inadequate, and still incomplete, as well as factors within the students and parents. Teachers' efforts to improve students' literacy skills through the reading corner are by utilizing existing facilities, and always providing motivation to students and increasing the number of books in the reading corner.